Status of padi drying operation and improvement strategy at LPN complex in Sekinchan Selangor, Malaysia - Ibrahim, Mohd. Nordin; Abdullah, Wan Mohamad (1987)
The entire Tanjung Karang rice growing area of about 20,000 hectares is served by four LPN integrated rice drying and milling complexes which are located in Sekinchan, Ulu Tiram Buruk, Kuala Selangor and Sungai Besar. The total amount of paddy received daily by the four complexes during peak period is about 1000 tonnes per day and this amount is shared between the four complexes in the ratio of 2:2:2:1 respectively. Field observations were carried out to assess the entire operations of the post harvest system within the vicinity of the LPN complexes at Sekinchan and Ulu Tiram Buruk. The post harvest system includes harvesting operation; activities at purchasing centers; transportation and delivery to LPN complexes; management, handling and drying operations mainly at Sekinchan LPN complex. Evaluation of these observations was done to identify specific problems and to offer alternatives for correction and improvement. The major problem is that the drying and handling capacity of the present main drying system (LSU Dryer) is able to meet only about 50% to 60% of the paddy delivered during peak periods (3 to 6 weeks). Since any effort to improve handling and drying efficients of the present system would not elleviate substantially the problem of undercapacity, it is therefore proposed to expand the drying capacity of the complex by incorporating a predrying section comprising of an additional system of dryer complete with handling and complementary tempering/temporary storage facilities. The improvement of the operation of the present system is also stressed. By this approach it is then forseen that the current drying backlog could be overcome.